2014
DOI: 10.1007/s00592-014-0598-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of continuous glucose monitoring on quality of life, treatment satisfaction, and use of medical care resources: analyses from the SWITCH study

Abstract: To investigate the impact of continuous glucose monitoring (CGM) on health-related quality of life (HRQOL), treatment satisfaction (TS) medical resource use, and indirect costs in the SWITCH study. SWITCH was a multicentre, randomized, crossover study. Patients with type 1 diabetes (n = 153) using continuous subcutaneous insulin infusion (CSII) were randomized to a 12 month sensor-On/Off or sensor-Off/On sequence (6 months each treatment), with a 4-month washout between periods. HRQOL in children and TS in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 20 publications
2
80
0
Order By: Relevance
“…7,14,[18][19][20][21] However, recent evidence suggests that rtCGM use in conjunction with MDI treatment may provide the similar glycemic benefits without the additional costs associated with CSII therapy. 22 Our study found that use of rtCGM was associated with reduced HbA1c and utilization of health services compared with SMBG use regardless of insulin delivery method.…”
Section: Discussionmentioning
confidence: 99%
“…7,14,[18][19][20][21] However, recent evidence suggests that rtCGM use in conjunction with MDI treatment may provide the similar glycemic benefits without the additional costs associated with CSII therapy. 22 Our study found that use of rtCGM was associated with reduced HbA1c and utilization of health services compared with SMBG use regardless of insulin delivery method.…”
Section: Discussionmentioning
confidence: 99%
“…A registry study of 17,317 participants confirmed that more frequent CGM use is associated with lower A1C (16), whereas another study showed that children with .70% sensor use missed fewer school days (17). Small randomized controlled trials in adults and children with baseline A1C 7.0-7.5% (53-58 mmol/mol) have confirmed favorable outcomes (A1C and hypoglycemia occurrence) in groups using CGM, suggesting that CGM may provide further benefit for individuals with type 1 diabetes who already have tight control (18,19).…”
Section: Continuous Glucose Monitoringmentioning
confidence: 99%
“…60 This is reassuring as there have been concerns that CGM data overload could have negative effects on QOL. 63,64 However its impact varies with age group, with trait anxiety higher in adolescents and lower in adults using CGM, compared with SMBG alone, 65 suggesting that CGM data may feel overwhelming in adolescents but empowering in adults.…”
Section: 52mentioning
confidence: 99%
“…62 Responders were also more likely than nonresponders to report their partner was interested in their CGM. 62 Several studies reported no QOL differences with SAPT, 57,61,63 but others found that SAPT improved diabetesspecific HRQOL (Hypoglycaemia Fear Survey Worry and Behaviour subscales) 58,59 and health and social functioning. 60 This is reassuring as there have been concerns that CGM data overload could have negative effects on QOL.…”
Section: 52mentioning
confidence: 99%